2010
DOI: 10.1007/s00259-010-1432-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammation of the left anterior descending coronary artery with cardiovascular risk factors, plaque burden and pericardial fat volume: a PET/CT study

Abstract: FDG uptake measurement in the LAD correlates with hypertension, coronary heart disease, BMI, PFV and CPB. However, due to myocardial FDG uptake these measurements are only feasible in one half of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…On the other hand, fatty acids are involved in intralesional lipid homeostasis and macrophage inflammatory responses through action of peroxisome proliferator-activated receptors and liver X receptors (3). Therefore, 11 C-acetate depicts molecular processes in a manner different from 18 F-FDG or choline compounds, which may be used to provide information about macrophage-mediated inflammation or cell membrane proliferation in atherosclerotic lesions (34,35). The increasing number of tracers available for the characterization of pathophysiologic processes in atherosclerotic plaque-and their complementary use-may eventually lead to a more thorough understanding of the complex interactions in the development and evolution of plaque.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fatty acids are involved in intralesional lipid homeostasis and macrophage inflammatory responses through action of peroxisome proliferator-activated receptors and liver X receptors (3). Therefore, 11 C-acetate depicts molecular processes in a manner different from 18 F-FDG or choline compounds, which may be used to provide information about macrophage-mediated inflammation or cell membrane proliferation in atherosclerotic lesions (34,35). The increasing number of tracers available for the characterization of pathophysiologic processes in atherosclerotic plaque-and their complementary use-may eventually lead to a more thorough understanding of the complex interactions in the development and evolution of plaque.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging role for nuclear medicine techniques such as PET/CT in assessing atherosclerosis by analyzing the biologic composition and pathophysiologic processes in atherosclerotic lesions (9,13,16,22). Common PET tracers currently in use or under investigation for assessment of atherosclerosis exhibit some inherent limitations.…”
Section: Comparison To Other Pet Tracers and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…18 F-FDG uptake in atherosclerotic lesions correlates with the presence of cardiovascular risk factors and might identify patients at risk for future vascular events (9,(12)(13)(14). Recently, several authors reported visualization of macrophage activity in atherosclerotic plaque using 18 Ffluorocholine and 11 C-choline PET/CT (15)(16)(17).…”
mentioning
confidence: 99%
“…They demonstrated higher FDG uptake in the stented segments in acute coronary syndrome, as well as in the relatively fixed left main coronary artery and the ascending aorta, consistent with a multifocal inflammatory response in unstable atherosclerosis. Published in 2010, Saam [80] measured FDG uptake in the coronary arteries of close to 300 subjects with cancer. Evaluation of coronary artery FDG uptake was only possible in half of those imaged; the remainder had myocardial FDG uptake that swamped any signal from the coronary plaque.…”
Section: Imaging the Coronary Arteriesmentioning
confidence: 99%